Sprzedawalem Churchilla i nafte - Lipinski, Adam. (Warszawa : Wydawn. Bellona, 1996)
The autobiography of a Polish nobleman who fought in WW II, traveled the world and became an oil magnate, who now lives in Nice.
Keywords: Lipinski, Adam